2018
DOI: 10.3390/ma11061009
|View full text |Cite
|
Sign up to set email alerts
|

Health Degradation Monitoring and Early Fault Diagnosis of a Rolling Bearing Based on CEEMDAN and Improved MMSE

Abstract: Rolling bearings play a crucial role in rotary machinery systems, and their operating state affects the entire mechanical system. In most cases, the fault of a rolling bearing can only be identified when it has developed to a certain degree. At that moment, there is already not much time for maintenance, and could cause serious damage to the entire mechanical system. This paper proposes a novel approach to health degradation monitoring and early fault diagnosis of rolling bearings based on a complete ensemble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 51 publications
(65 reference statements)
0
51
0
Order By: Relevance
“…where T and stand for the range statistics and the semiquadratic statistic, respectively, and both statistics are based on the t-statistics as shown in (35)- (36). These two statistics (T and ) are mainly to remove the model whose p-value is less than the significance level .…”
Section: Evaluation Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…where T and stand for the range statistics and the semiquadratic statistic, respectively, and both statistics are based on the t-statistics as shown in (35)- (36). These two statistics (T and ) are mainly to remove the model whose p-value is less than the significance level .…”
Section: Evaluation Criteriamentioning
confidence: 99%
“…Later, the authors put forward an improved version of CEEMDAN to obtain decomposed components with less noise and more physical meaning [33]. The CEEMDAN has succeeded in wind speed forecasting [34], electricity load forecasting [35], and fault diagnosis [36][37][38]. Therefore, CEEMDAN may have the potential to forecast crude oil prices.…”
Section: Introductionmentioning
confidence: 99%
“…To alleviate these phenomena, CEEMDAN [14] was introduced to decompose non-liner and non-stationary signals. Currently, this method is also widely applied in the fault diagnosis domain to obtain feature information on vibration signals [47,48]. The following is the basic principle of CEEMDAN:…”
Section: Ceemdan Algorithmmentioning
confidence: 99%
“…Energy variation of the 3× component (where X represents the frequency corresponding to the rotating speed) extracted based on Wavelet Packet Transform [43][44][45] was used to quantify the crack depth of a crack with known crack location in a rotor by Gómez et al [46], and the analytical Jeffcott rotor model and the corresponding experimental rotor with a saw-cut crack were studied to validate the method. EMD method [47][48][49] was applied to steady-state responses generated from a Jeffcott rotor to extract the 3× and 2× components in the neighborhood of 1/3 and 1/2 of the critical rotating speed by Guo et al [50], results showed that the variation of averaged amplitudes of super-harmonic components provided clear and robust signatures of early cracks in rotating rotors. However, from the literature, few researches have been carried out to identify both the location and depth of a crack in a rotor with these super-harmonic features.…”
Section: Introductionmentioning
confidence: 99%